2016
DOI: 10.1128/jvi.01410-15
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus (EBV) Tegument Protein BGLF2 Promotes EBV Reactivation through Activation of the p38 Mitogen-Activated Protein Kinase

Abstract: IMPORTANCE Epstein-Barr virus (EBV) is associated with both B cell and epithelial cell malignancies, and the virus activates multiple signaling pathways important for its persistence in latently infected cells. We identified a viral tegument protein, BGLF2, which activates members of the mitogen-activated protein kinase signaling pathway. Expression of BGLF2 increased expression of EBV BZLF1, which activates a switch from latent to lytic virus infection, and increased production of EBV. Inhibition of BGFL2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 62 publications
7
52
0
Order By: Relevance
“…Indeed, studies of the UL16 homolog from a gammaherpesvirus (Epstein-Barr virus) have shown that it can multimerize in transfected cells (61). We used coimmunoprecipitation and colocalization assays to look for interactions among tagged derivatives of full-length UL16, but these experiments did not yield convincing results (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of the UL16 homolog from a gammaherpesvirus (Epstein-Barr virus) have shown that it can multimerize in transfected cells (61). We used coimmunoprecipitation and colocalization assays to look for interactions among tagged derivatives of full-length UL16, but these experiments did not yield convincing results (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…BGLF2 is a tegument protein that expressed with late kinetics in EBV-infected cells (33,64,65). Recently, BGLF2 has been shown to activate p38 and JNK signaling pathways and enhance AP-1-dependent transcription (34,35). Several orthologs of BGLF2, such as Kaposi's sarcomaassociated herpesvirus ORF33 (66,67), varicella-zoster virus ORF44 (68), and cytomegalovirus (CMV) unique long 94 (UL94) (69), are essential for viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential tegument protein, BGLF2 is important for the re-envelopment of EBV in the cytoplasm or plasma membrane, which can be detected in the mature virions (33). It has been reported that BGLF2 can increase EBV infectivity by activating the AP-1 signaling pathway through phosphorylation of p38 and JNK (34,35). However, whether BGLF2 is involved in regulating NF-kB signaling is still unknown.…”
mentioning
confidence: 99%
“…In an earlier study, the BMRF1 protein was found to directly interact with Zta in vitro as well as in vivo , enhancing transcription from their common early BHLF1 promoter 76. Similarly, EBV tegument protein BGLF2, encoded in the late phase of the lytic cycle, was suggested to enhance Zta expression through activation of the p38 signaling pathway 77.…”
Section: The Viral Self-regulation Of Ebv Reactivationmentioning
confidence: 99%